AN OVERVIEW OF MALAYSIAN HALAL CERTIFICATION AMONG MICRO-ENTERPRISES - Nur Syammimi Mat Puad; Mohammad Aizat Jamaludin; Betania Kartika (Journal of Islamic, Social, Economics and Development, 2024)
The swift advancement of the Halal industry in Malaysia can be attributed to the pivotal role played by Halal certification in propelling business performance. Malaysian Halal certification has attained global renown for signifying safety, ensuring high-quality standards, and guaranteeing wholesomeness in Halal-certified products and services. While larger corporations adeptly navigate the Halal certification process, micro-enterprises encounter distinctive challenges. This article aims to analyse the overview of Halal certification for micro-enterprises in Malaysia, exploring its significance, challenges, and opportunities. Employing the library research method, this research synthesizes pertinent information from secondary sources to fulfil its research objectives. The findings of this article clarify the primary challenges impeding broader application of Halal certification among micro-enterprises are financial constraints, intricate application procedures for Halal certification, and lack of awareness regarding Halal-certified products. Notably, this article highlights the opportunity for micro-entrepreneurs to enhance their enterprises significantly through the attainment of Halal certification recognition. In conclusion, the study asserts that the Malaysian Halal certification is imperative for micro-enterprises to effectively market their products and emerge as a lucrative promotional instrument.